2021
DOI: 10.3390/foods10081921
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Whole Grain Sorghum and Their Health Benefits

Abstract: Sorghum grain (Sorghum bicolor L. Moench) is a staple food grown across the globe, and is mainly cultivated in the semi-arid regions of Africa and Asia. Recently, sorghum grain is increasingly utilized for human consumption, due to the gluten-free nature and potential phenolic-induced health benefits. Sorghum grain is rich in bioactive phenolic compounds, such as ferulic acid, gallic acid, vanillic acid, luteolin, and apigenin, 3-deoxyanthocyanidins (3-DXA), which are known to provide many health benefits, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 68 publications
(117 reference statements)
1
50
1
2
Order By: Relevance
“…Sorghum is rich in bioactive phenolic compounds such as ferulic acid, gallic acid, and vanillic acid, which are known to provide many health benefits, including antioxidant anti-inflammatory effects. Given the growing trend in human consumption, sorghum is being used more and more often for the production of functional food [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum is rich in bioactive phenolic compounds such as ferulic acid, gallic acid, and vanillic acid, which are known to provide many health benefits, including antioxidant anti-inflammatory effects. Given the growing trend in human consumption, sorghum is being used more and more often for the production of functional food [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Las kafirinas representan del 70 al 80% de las proteínas totales en el grano y se dividen en α-Kafirinas (80%) que tienen un peso molecular de 25 a 23 kDa, β-Kafirinas (8 a 13%) con pesos moleculares de 16, 18, and 20 kDa, γ-Kafirinas (9 a 21%) con pesos moleculares entre 20 y 28 kDa y en menor proporción, δ-Kafirinas con un peso molecular de 13 kDa. Las kafirinas están estrechamente relacionadas con la calidad y digestibilidad del sorgo y los alimentos que se derivan de este cereal (Badigannavar et al, 2016;Li et al, 2018;Balandrán-Quintana et al, 2019;Castro-Jácome et al, 2020;Xu et al, 2021).…”
Section: Proteínasunclassified
“…Además, el sorgo tiene un gran potencial para ser utilizado como ingrediente funcional en el desarrollo de nuevos productos por su alto contenido de fibra dietética y compuestos bioactivos (Tabla 2). La presencia de compuestos bioactivos en el sorgo otorgan beneficios a la salud relacionados con propiedades funcionales como la actividad antioxidante, antihipertensiva, antidiabética y antiobesidad, entre otras (Figura 5) (Taylor, et al, 2006;Awika, 2017;Xu et al, 2021).…”
Section: Propiedades Bioactivas De Alimentos a Base De Sorgounclassified
“…In a previous study, widespread medical and food uses of bioactive compounds in grain and sweet sorghum varieties has been reviewed [ 16 ]. Xu et al [ 106 ] also reported that sorghum grain were rich in phenolic compounds, such as ferulic acid, gallic acid, etc. The concentration of p -coumaric and ferulic acids in stalk bark and pith of sweet sorghum were also measured, and stalk bark showed higher yields of p -coumaric and ferulic acids after alkaline hydrolysis at 170 ℃ [ 107 ].…”
Section: Introductionmentioning
confidence: 99%